1983
DOI: 10.1152/ajpgi.1983.245.2.g208
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal regulation of pancreatic exocrine function in vitro by somatostatin-28

Abstract: The action of natural and synthetic somatostatin-(1--28), [Nle8]somatostatin-(1--28), somatostatin-(15--28), and somatostatin-(1--14) was examined in dispersed acini from guinea pig pancreas. At high concentrations, the 28-amino acid form of somatostatin increased amylase release, outflux of 45Ca, cellular cGMP, and to a lesser extent cellular cAMP. The increase in amylase release was suppressed by dibutyryl cGMP but was not modified by theophylline or atropine. Binding of 125I-labeled [Thr28, Nle31] cholecyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…Furthermore, a previous study has shown that cyclic AMP-dependent protein phosphorylation initiates the acquisition of Ca 2ϩ -sensitivity by the insensitive Ca 2ϩ activated K ϩ channel in guinea-pig pancreatic acinar cells [29]. A single application of somatostatin has been reported to have no effect on resting cyclic AMP-level [13], but it can inhibit cyclic AMP formation induced by secretin in pancreatic acinar cells [15]. These results coincide with ours.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, a previous study has shown that cyclic AMP-dependent protein phosphorylation initiates the acquisition of Ca 2ϩ -sensitivity by the insensitive Ca 2ϩ activated K ϩ channel in guinea-pig pancreatic acinar cells [29]. A single application of somatostatin has been reported to have no effect on resting cyclic AMP-level [13], but it can inhibit cyclic AMP formation induced by secretin in pancreatic acinar cells [15]. These results coincide with ours.…”
Section: Discussionsupporting
confidence: 90%
“…However, its inhibitory effect of somatostatin on the activity of the channel was not complete, suggesting another pathway, if any, being involved. Somatostatin has been reported to induce a production of cyclic GMP in the pancreatic acinar cells [15], and cyclic GMP-dependent kinase has been reported to regulate Islet Hormones Regulate K ϩ Channel Table 4. The mean؎SEM of open-state probability (p) about the effect of somatostatin on a forskolin-induced opening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, somatostatin does not inhibit amylase secretion from isolated acini stimulated by caerulein, secretin, vasoactive intestinal polypeptide or carbachol. High doses of somatostatin also stimulate enzyme secretion from isolated acini (Esteve, Vaysse, Susini, Kunsch, Fourmy, Pradayrol, Wunsch, Moroder & Ribet, 1983). Similarly, pancreatic polypeptide, neuropeptide Y and peptide YY inhibit pancreatic exocrine secretion in the intact rat (Louie, Williams & Owyang, 1985).…”
Section: Isolated Vascularly Perfused Pancreasmentioning
confidence: 92%
“…It has been shown that somatostatin does not inhibit enzyme secretion in either isolated arterially perfused preparations or acinic cells in vitro (1,6,23,27,40,41), suggesting that the mechanism of inhibition of pancreatic exocrine secretion is indirect. Indeed, there is evidence that somatostatin is likely to exert the inhibitory effect via a central vagal site (19), the sympathetic nerve (22), an intrapancreatic cholinergic pathway (16), or the intrinsic pancreatic peptidergic neurons (26).…”
mentioning
confidence: 99%